The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1984-82502013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in lawsuits for drugs

Abstract: The aim of this study was to characterize the lawsuits requesting drugs considering the economic profile of their petitioners. All lawsuits (1378) accepted against Goiânia, GO from 2003 to 2007 were analyzed. Petitioners' demographic characteristics, reported diseases, requested drugs, origin of healthcare service, and lawsuit agent were described. Complainants' addresses were georeferenced and distributed into 4 regional groups classified in accordance with the population's average income. Dwellers of wealthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
5
9
0
1
Order By: Relevance
“…It was observed that institutional strategies that work in an interinstitutional manner are effective in mitigating some of the side effects of the judicialization of the right to health, such as a reduction in the filing of new lawsuits and that people who really need access to medicines now have more barriers. A similar reduction was also observed in a previous study in Brazil [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was observed that institutional strategies that work in an interinstitutional manner are effective in mitigating some of the side effects of the judicialization of the right to health, such as a reduction in the filing of new lawsuits and that people who really need access to medicines now have more barriers. A similar reduction was also observed in a previous study in Brazil [30].…”
Section: Discussionsupporting
confidence: 91%
“…The lawsuit data were collected using a form standardized by the researchers after reviewing variables that were investigated in a prior study done in Brazil [30], which included the following: (i) sociodemographic characteristics and the disease(s) of the plaintiffs; (ii) characteristics of the medications solicited in the lawsuits; and (iii) the institutional strategies.…”
Section: Variablesmentioning
confidence: 99%
“…It was observed that institutional strategies that work in an interinstitutional manner are effective in mitigating some of the side effects of the judicialization of the right to health, such as a reduction in the filing of new lawsuits and that people who really need access to medicines now have more barriers. A similar reduction was also observed in a previous study in Brazil [30]. For the justice system, the reduction of the procedural burden involving requests for medicines can contribute to a reduction in the administrative cost of lawsuits, such as employee expenses, consumables, paper, etc.…”
Section: Discussionsupporting
confidence: 85%
“…The lawsuit data were collected using a form standardized by the researchers after reviewing variables that were investigated in a prior study done in Brazil [30], which included the following: (i) sociodemographic characteristics and the disease(s) of the plaintiffs; (ii) characteristics of the medications solicited in the lawsuits; and (iii) the institutional strategies. The variables related to the interventions were determined according to previously published studies [35,36].…”
Section: Variablesmentioning
confidence: 99%
“…It was observed that institutional strategies that work in an interinstitutional manner are effective in mitigating some of the side effects of the judicialization of the right to health, specifically for the access to medicines, such as in the reduction in the filing of new lawsuits. A similar reduction was also observed in a previous study in Brazil [30]. For the justice system, the reduction in the procedural burden involving the requests for medicines can contribute to a reduction in the administrative cost of lawsuits, such as: employee expenses, consumables, paper and etc.…”
Section: Discussionsupporting
confidence: 85%